The obligation to obey the law: exploring national differences - Rooij, Benjamin van (Crime, law and social change, 2024)
People vary in the extent to which they generally feel obligated to obey the law. The Obligation to Obey the Law (OOL) plays a major role in how people respond to legal rules and whether they comply or violate such rules. Most existing research on OOL has been non-comparative. The present paper explores national differences in OOL by analyzing data from a survey conducted among a convenience sample (n = 716) of law students in the Netherlands, the US, Israel, and China. In contrast to what existing research on procedural justice and OOL would lead us to expect, the data do not reveal significant differences in OOL across markedly different national populations. It explores why no such differences have been found and what the implications of these findings are for our understanding of OOL and compliance more broadly.